The Influence of Career Development, Job Loyalty and Employee Welfare on Employee Performance in National Unity and Political Agencies in South Minahasa - Vicky Ratulangi; Lucky O. H. Dotulong; Raymond Ch. Kawet (International Journal of Economics Accounting and Management, 2024)
This research aims to determine the influence of career development, job loyalty and Employee Welfare on employee performance at the National Unity and Political Agency of South Minahasa. This research uses quantitative and associative methods. The sampling technique in this research used saturated samples. Data collection in this research used a questionnaire distributed to 35 respondents who were KESBANGPOL Agency employees. The results show that career development, job loyalty and employee welfare simultaneously have a significant effect on the performance of employees of the National Unity and Political Agency of South Minahasa. Career development partially and significantly influences the performance of employees of the South Minahasa National and Political Unity Agency. Job loyalty partially and significantly influences the performance of employees of the National Unity and Political Agency of South Minahasa. Employee welfare partially and significantly influences the performance of employees of the National Unity and Political Agency of South Minahasa. It can be concluded that Career Development, Job Loyalty and Employee Welfare simultaneously have a positive and significant effect on the performance of employees of the South Minahasa National and Political Unity Agency, while the variables of career development, job loyalty and employee welfare partially have a positive and significant effect on the performance of National Unity and Political Agency employees. South Minahasa Politics. For the National Unity and Political Agency of South Minahasa, the variables of career development, job loyalty, and employee welfare have been proven to influence employee performance